A Quotient of Independent Measurements as Outcome - Kron, Martina; Schneckenburger, Herbert; Gschwend, Michael H; Josef, Högel (Arzneimittelforschung, 2000)
The methodology in this paper was proposed to analyze biological data. The variable of interest, W, was a quotient of measurements; W: = X/(Y · Z). The peculiar problem was that X, Y, and Ζ could only be determined in three independent units of observation which were destroyed in the course of each measurement. A test statistic for the comparison of two treatments in W is proposed which is based on robust measures of location and dispersion in order to account for outliers in the data. Simulations showed that the test statistic proposed is approximately normally distributed, even for small sample sizes.
Keywords: Quotient of independent random variables, multiple testing, outliers, robust; measures of location and dispersion